Retinal hypoxia after experimental subarachnoid hemorrhage. (18th January 2021) - Zhaba, Wang-Dui; Deji, Qu-Zhen; Deng, Hong-Ji; Han, Yan-Ling; Gao, Sheng-Qing; Liu, Xi-Lin; Zhou, Meng-Liang
Highlights: There is a noticeable reduction of retinal ganglion cells after subarachnoid hemorrhage. Subarachnoid hemorrhage causes retinal new vessels in the retinal ganglion cells layer. HIF-1α/VEGF-A pathway is activated in the retina after subarachnoid hemorrhage. Abstract: Background and Purpose: The patients who survive subarachnoid hemorrhage (SAH) often have long-term neurological complications. There are no reports about the pathological change of retina after SAH. Methods: An experimental model of SAH was established by injecting autologous blood into the prechiasmatic cistern of Sprague-Dawley rats. Hematoxylin and eosin (HE) staining was performed to show the alternation of morphology in retina after SAH. To detect the retinal new vessels (NVs), CD31 was labelled by immunofluorescence and immunohistochemistry. The time-course expressions of vascular endothelial growth factor (VEGF)-A and hypoxia-inducible factor-1α (HIF-1 α) was also revealed by Western blot analysis. Results: A clear reduction of retinal ganglion cells (RGCs) was noticed after SAH. The immunofluorescence and immunohistochemical staining of CD31 reveals a large number of NVs in RGC layer after SAH compared with the normal controls. The level of VEGF-A in the retina after SAH was increased and peaked at 12h and 14 d. The expression of HIF-1α in the retina increased as early as 3 h after SAH, reached a peak at 12 h after SAH. Conclusions: The results showed that SAH induced the retina hypoxia resulting in the reduction of RGCs, increase of NVs and activation of NVs related HIF-1α/VEGF-A pathway.